La importancia de las destrezas legales en la actualidad - Ezcurra, Huáscar; Jara, José María de la; Flor, Nicolás de la; Mori, Pablo (Pontificia Universidad Católica del Perú, 2015)
In recent years, the attention of lawyers and Law students in the legal skills has greatly increased.In this round table, the rapporteurs deliberate about their possible limits, regulation and enforcement, and give a vision about the future of the practice of Law.

En los últimos años, se ha incrementado notablemente el interés de abogados y estudiantes de Derecho por las destrezas legales.En esta mesa, los ponentes reflexionan sobre sus límites, regulación y aplicación, y dan una visión del futuro del ejercicio del Derecho.
The importance of legal skills nowadays
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01